Learn from the Experts about AI Monica Rogati - Rogati, Monica (O'Reilly Media, Inc., 2018)
Learn from the Experts is a series where we sit down with leading industry practitioners and ask them for real-world stories and examples of how they're using technology in their everyday work. In this interview, Jeff Bleiel talks to Monica Rogati about what AI can do for businesses, and the role of AI in a business strategy.